Analisis Spasial Pneumonia Balita Berdasarkan Cakupan Imunisasi Dasar Lengkap (IDL) dan Prevalensi Balita Gizi Kurang di Provinsi Bali Tahun 2022-2024 - Putri Qanita Aulianur (Yayasan Literasi Sains Indonesia, 2026)
Pneumonia is an acute infection of the pulmonary parenchyma encompassing the alveoli and interstitial tissue, caused by various pathogens such as viruses, fungi, or parasites, with the exception of Mycobacterium tuberculosis. Pneumonia is frequently encountered in children, affecting the lower respiratory tract, and its primary clinical manifestations include cough, fever, dyspnea, and reduced physical activity. This study was conducted using an analytic observational method with an ecological study design. Data were obtained from the Health Profile of the Bali Provincial Health Office for the years 2022–2024. The study sample comprised eight districts and one municipality located within Bali Province. The software utilized in this study included QGIS and GeoDa, employing Queen Contiguity matrix weighting. The Bivariate Local Indicators of Spatial Association (BiLISA) results indicated that complete basic immunization coverage yielded a p-value of 0.389 and a z-value of 0.2929, whereas the prevalence of undernutrition among children under five yielded a p-value of 0.175 and a z-value of 1.0016. Both variables shared an identical expected index value E(I) of −0.125. The study concluded that no statistically significant spatial association existed between complete basic immunization coverage and the prevalence of undernutrition with the incidence of pneumonia among children under five (p-value > 0.05), with the strength of association classified as weak.